IJCM_404A: Newborn deaths in Maharashtra: A qualitative thematic analysis of newspaper articles - Shet Neha Nitin; Raul Mayuri; Sable Rupali (Wolters Kluwer Medknow Publications, 2024)
Background: As per statistics on infant mortality, the State of Maharashtra has done well in bringing down IMR from 33 to 16 per 1000 live births. However, in recent years many incidents come to light, especially in the case of institutional deliveries where newborns die either due to infrastructure failure or dysfunctional equipment. On a programmatic level, this has serious implications. Schemes such as Janani Suraksha Yojana promote institutional deliveries, but the institutes are unable to tend to the patient load efficiently. Analysing newspaper articles covering such incidents will throw light on actionable points for policy change. Experts from various fields tend to author such articles. Therefore it's imperative to search every source available to bottleneck the areas for improvement. Objective: 1. To understand the perspectives of authors about newborn deaths in Maharashtra 2. To derive major areas of concern raised by such articles possibly causing newborn deaths in Maharashtra Methodology: All newspaper articles published in the last 2 years about newborn deaths in Maharashtra were identified. They were segregated according to the Name of the newspaper, author, incident, period etc. A thematic analysis was performed on 12 such articles to uncover different themes and sub themes. Results: Major themes that emerged were related to infrastructure issues and equipment failure. Another important theme was the higher patient load on secondary care due to excessive referrals from primary health facilities. The schemes promoting institutional deliveries did not anticipate the additional workload on district and subdistrict hospitals. Strengthening primary care remains the major area of concern. Conclusion: Lack of quality assurance is the major bottleneck at the infrastructure level. Strengthening primary care will reduce the excessive workload on district and subdistrict hospitals. All these are part of the same chain of events.